A representação de Antônio Conselheiro na literatura de cordel : leitura das obras de Rodolfo Coelho Cavalcante, Minelvino Francisco Silva e Geraldo Amâncio - Oliveira, Jessica Melo de (2019)
In this work, it is proposed to reflect, as the popular Literature of cordel produced in different times represents the figure of Antônio Conselheiro. More specifically, we study the poetry of the leaflets: Antônio Conselheiro History and the Canudos War (1977), Minelvino Francisco Silva's line; Antônio Conselheiro, the holy warrior of Canudos (1977), by Rodolfo Coelho Cavalcante; and the History of Antônio Conselheiro (2010), the line of Geraldo Amâncio. These productions carried out in distinct periods constitute private speeches and representations of the Blessed One, since each string presents the Conselheiro in a singular way. In the early works of Cavalcante and Francisco da Silva, Ceará was adjectivized as a mad, messianic fanatic and responsible for the clash. On the other hand, in the booklets of Amâncio, the conselheiro appears like a visionary figure of Belo Monte, who defended the earth and resisted to the coronelista system. In this context, the brochures reflect different representations, being possible to understand and to reflect the various interpretations and versions made on the conflict. Since all these versions presented by popular literature are necessary to reflect on the concepts that were formed around this event. Within this context, the cordel, which discusses the Belo Monte as thematic serves as historical source for the Academy. As well, the cordel by its historical importance, is considered “the most popular document” of the sertão. Thus, the aforementioned leaflets have a critical social vision, besides incorporating aspects such as culture, orality, history and Northeastern identity. All this serves for the sertanejo to understand his reality. Therefore, in analyzing Antônio Conselheiro representation in cordel literature, it is important to seek the theoretical contribution of Edmundo Moniz (1984), Rogério Souza Silva (2001), Lindiane Santos de Lima Pinheiro (2015), Franklin Maxado (1980), Luís da (1998), Wellington Freire (2017), Joseph M. Luyten (1983), Berthold Zilly (1996), José de Ribamar Lopes (1994), Maria Ângela de Faria (1996), and the use of the term Edilene Matos (1986), Eno Teodoro Wanke (1983), Jairo Carvalho de Nascimento (2008), Rute Brito Terra (1983), Pedro Lima Vasconcellos (2019) and others. Thus, the literary fiction, as literary production, through its images resignifies the memory of historical figures, which are striking and unique in the backlands.